Antioxidant activities, dietary nutrients, and yield potential of bitter gourd (Momordica charantia L.) lines in diverse growing environments - Jat, Gograj Singh; Behera, Tusar Kanti; Singh, Awani Kumar; Bana, Ram Swaroop; Singh, Deepak; Godara, Samarth; Reddy, Umesh K.; Rao, P. Gangadhara; Ram, H.; Vinay, N. D.; Kumar, Sachin; Tomar, Bhoopal Singh (Frontiers in Nutrition, 2024)
The biotic and abiotic stresses cause a significant decline in yield and fruit quality traits including antioxidants and minerals of bitter gourd under open field grown crop. Protected cultivation technology has emerged to minimize such stresses. We investigated the effect of diverse environments (Hi-tech green-house, naturally ventilated-polyhouse, insect-proof net-house and open field scenario) and breeding lines on earliness, yield potential, antioxidant activities and dietary nutrients. In the GYT analysis, 12 treatment combination effects involving four raising environments and three breeding lines of bitter gourd were examined. The 3-years study suggested that cultivation of bitter gourd crop under insect proof net house (NH) showed superior performance for earliness, yield attributing traits, antioxidant activities and dietary nutrients followed by naturally ventilated polyhouse (NP). However, NH was at par with the NP and significantly greater than the open field grown crop. The GYT biplot analysis highlighted that the combinations of NH and Pusa Rasdar outperformed and found most stable treatment for all the traits investigated followed by NH in conjunction with S32 and S57 lines. This study suggests that growing of bitter gourd under protected environments is the optimal strategy to fetch an early price in the market as well as to improve yield and nutritional quality of fruits.